English Language Teaching in Islamic Primary Education under Cambodia’s MoEYS Curriculum - Ulya Himawati; Ersila Devy Rinjani; El Yakin; Muhammad Ahsanul Husna (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2025)
This study examines English language teaching practices in Islamic primary education under Cambodia’s national curriculum, regulated by the Ministry of Education, Youth and Sport (MoEYS). Conducted in an Islamic primary school within a Muslim-minority context, the study addresses the gap between national curriculum policy and classroom practice. Employing a descriptive qualitative research design, data were collected through classroom observations, semi-structured interviews with school leaders and English teachers, and document analysis. The findings reveal that while English instruction generally aligns with national curriculum objectives, teachers actively adapt teaching materials, classroom strategies, and learning contexts to ensure cultural and religious appropriateness. Islamic values are implicitly integrated through teacher modeling and interaction patterns rather than through explicit religious instruction. From a policy implementation perspective, the findings demonstrate a clear gap between policy as intended and policy as implemented, with teachers functioning as key mediators who exercise professional discretion in enacting curriculum policy. This study contributes empirical insights into English language teaching in Islamic primary education within a secular national system. It highlights the importance of teacher agency in bridging policy demands and faith-based educational contexts.